From stimulus to science - Quine, W. V. (Willard Van Orman) (Harvard University Press, 1995)
In this short book, based on lectures delivered in Spain in 1990, Quine begins by locating his work historically. He provides a lightning tour of the history of philosophy (particularly the history of epistemology), beginning with Plato and culminating in an appreciative sketch of Carnap's philosophical ambitions and achievements. This leads, in the second chapter, to an introduction to Quine's attempt to naturalize epistemology, which emphasizes his continuities with Carnap rather than the differences between them. The next chapters develop the naturalistic story of the development of science to take account of how our conceptual apparatus is enhanced so that we can view the world as containing re-identifiable objects.